2008
DOI: 10.1007/s00412-008-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated cytogenetic map of mitotic metaphase chromosome 9 of maize: resolution, sensitivity, and banding paint development

Abstract: To study the correlation of the sequence positions on the physical DNA finger print contig (FPC) map and cytogenetic maps of pachytene and somatic maize chromosomes, sequences located along the chromosome 9 FPC map approximately every 10 Mb were selected to place on maize chromosomes using fluorescent in situ hybridization (FISH). The probes were produced as pooled polymerase chain reaction products based on sequences of genetic markers or repeat-free portions of mapped bacterial artificial chromosome (BAC) cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…These results suggested that an ancient chromosome rearrangement occurred between the two duplicated regions of C4B in either the A or C genomes after the diversification from a common ancestor. The future of plant molecular cytogenetics is promising in terms of both methods and applications (Kato et al 2005;Walling et al 2005;Lamb and Birchler 2006;Danilova and Birchler 2008;Guerra 2008;Pires and Hertweck 2008;Lysak et al 2010;Xiong et al 2010). The robust novel chromosomal painting technique developed here will assist the understanding of chromosome pairing, homoeologous recombination, and genome evolution in the genus Brassica and will facilitate new applied breeding technologies in this genus that rely upon identification of individual chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that an ancient chromosome rearrangement occurred between the two duplicated regions of C4B in either the A or C genomes after the diversification from a common ancestor. The future of plant molecular cytogenetics is promising in terms of both methods and applications (Kato et al 2005;Walling et al 2005;Lamb and Birchler 2006;Danilova and Birchler 2008;Guerra 2008;Pires and Hertweck 2008;Lysak et al 2010;Xiong et al 2010). The robust novel chromosomal painting technique developed here will assist the understanding of chromosome pairing, homoeologous recombination, and genome evolution in the genus Brassica and will facilitate new applied breeding technologies in this genus that rely upon identification of individual chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The FISH resolution on condensed mitotic chromosomes is not very high. The axial resolution of FISH on maize somatic chromosome is 3-8 Mb, but it is possible to distinguish separate FISH signals that are about 200 kb apart (Danilova and Birchler 2008). Double Acc-2 FISH signals were observed on chromosomes 3A, 3D, 3B, and 4A of bread wheat; 4A t and 3G of T. timopheevii; and 3D of Ae.…”
Section: Fish Mapping Of Acc-2 Genesmentioning
confidence: 99%
“…For genomes enriched with repeats, a repeat-free probe for a particular genic region either can be produced from cDNA or developed from genomic DNA by sequence analysis and PCR amplification of the repeat-free region, and used in direct FISH as was shown in maize (Wang et al 2006;Lamb et al 2007;Danilova and Birchler 2008) and barley (Ma et al 2010). In direct FISH, fluorochromes are incorporated directly into DNA probes and the procedure does not need detection step.…”
Section: Introductionmentioning
confidence: 99%
“…However, they require long incubation periods, up to 2 h or more with some species (De Melo and Guerra, 2003;Marcon et al, 2005). Aiming to achieve a faster or more efficient results, other enzymes have been used, such as macerozyme (Fukui and Nakayama, 1996), pectolyase and cellulase Onozuka RS (Danilova and Birchler, 2008;Yuan and Tomita, 2009), Ultrazym (Almeida and Carvalho, 2004), and Pectinex (Viccini et al, 2006;Guimarães et al, 2009), among others.…”
Section: Introductionmentioning
confidence: 99%